In-situ electron and ion measurements and observed gravity wave effects in the polar mesosphere during the MaCWAVE program - C. L. Croskey; J. D. Mitchell; M. Friedrich; F. J. Schmidlin; R. A. Goldberg (Annales Geophysicae, 2006)
Langmuir probe electron and ion measurements from four instrumented rockets flown during the MaCWAVE ( M ountain a nd C onvective W aves A scending VE rtically) program are reported. Two of the rockets were launched from Andøya Rocket Range, Norway, in the summer of 2002. Electron scavenging by ice particulates produced reductions of the electron density in both sharp narrow (≈1–2 km) layers and as a broad (≈13 km) depletion. Small-scale irregularities were observed in the altitude regions of both types of electron depletion. The scale of the irregularities extended to wavelengths comparable to those used by ground-based radars in observing PMSE. In regions where ice particles were not present, analysis of the spectral signatures provided reasonable estimates of the energy deposition from breaking gravity waves. Two more instrumented rockets were flown from Esrange, Sweden, in January2003. Little turbulence or energy deposition was observed during one flight, but relatively large values were observed during the other flight. The altitude distribution of the observed turbulence was consistent with observations of a semidiurnal tide and gravity wave instability effects as determined by ground-based lidar and radar measurements and by falling sphere measurements of the winds and temperatures (Goldberg et al., 2006; Williams et al., 2006).